2017
DOI: 10.1111/1748-8583.12149
|View full text |Cite
|
Sign up to set email alerts
|

Advancing interests through informal voice: a study of professional workers in Sri Lanka's knowledge outsourcing sector

Abstract: Drawing on a rhetorical approach, this article examines how early career professional workers challenge ‘ideal worker expectations’ through informal voice. Informal ‘voice’ is shown as a powerful way of advancing workers' interests, leading to incremental changes that improve their conditions of work. Striking are the power dynamics underpinning informal voice. Highlighting how ideal worker expectations are continuously legitimised and de‐legitimised as employees and their managers rhetorically engage with eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…One can change topics of conversation, thereby effectively removing certain issues from the agenda altogether (Billig, 1996). It is important to recognize that persuasion is also influenced by the perceived authority, credibility (Giles and Coupland, 1991), exposure and expertise (Fernando, 2017) of speakers.…”
Section: Rhetorical Persuasionmentioning
confidence: 99%
See 2 more Smart Citations
“…One can change topics of conversation, thereby effectively removing certain issues from the agenda altogether (Billig, 1996). It is important to recognize that persuasion is also influenced by the perceived authority, credibility (Giles and Coupland, 1991), exposure and expertise (Fernando, 2017) of speakers.…”
Section: Rhetorical Persuasionmentioning
confidence: 99%
“…Studies have drawn on theoretical ideas of rhetoric to offer explanations into how ordinary employees undermine and invalidate normative organizational discourses (Nentwich and Hoyer, 2012;Symon, 2005). Research in this area has also shown how individuals challenge the assumptions underpinning normative discourses, and rework them in an effort to create new organizational realities (Fernando, 2017). In a study of the Financial Accounting Standards Board (FASB), Young (2003) demonstrates how rhetorical persuasion is used to both maintain dominant accounting practices and silence alternatives to, and criticisms of, those practices.…”
Section: Rhetorical Persuasionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first that identifies power dynamics in the ITO supply chain as an external factor that influences suppliers' talent retention. It hereby enriches our knowledge of the contextual factors shaping the HR practices of supplier firms and the ensuing employee outcomes (Fernando, 2017; Kanwar et al. , 2012).…”
Section: Discussionmentioning
confidence: 86%
“…We chose China because it represents an under-researched context for the topic of talent retention in ITO supply chain, compared with relatively abundant research efforts in the context of Anglophone or South Asian countries (e.g. Fernando, 2017; Kiessling et al. , 2012; Presbitero et al.…”
Section: Introductionmentioning
confidence: 99%